Phytosulfokine-α, a sulfated pentapeptide, stimulates the proliferation of rice cells by means of specific high- and low-affinity binding sites - Matsubayashi, Yoshikatsu (The National Academy of Sciences of the USA, 1997)
Peptide growth factors were isolated from conditioned medium derived from rice (Oryza sativa L.) suspension cultures and identified to be a sulfated pentapeptide [H-Tyr(SO(3)H)-Ile-Tyr(SO(3)H)-Thr-Gln-OH] and its C-terminal-truncated tetrapeptide [H-Tyr(SO(3)H)-Ile-Tyr(SO(3)H)-Thr-OH]. These structures were identical to the phytosulfokines originally found in asparagus (Asparagus officinalis L.) mesophyll cultures. The pentapeptide [phytosulfokine-α (PSK-α)] very strongly stimulated colony formation of rice protoplasts at concentrations above 10(−8) M, indicating a similar mode of action in rice of phytosulfokines. Binding assays using (35)S-labeled PSK-α demonstrated the existence of both high- and low-affinity specific saturable binding sites on the surface of rice cells in suspension. Analysis of [(35)S]PSK-α binding in differential centrifugation fractions suggested association of the binding with a plasma membrane-enriched fraction. The apparent K(d) values for [(35)S]PSK-α binding were found to be 1 × 10(−9) M for the high-affinity type and 1 × 10(−7) M for the low-affinity type, with maximal numbers of binding sites of 1 × 10(4) sites per cell and 1 × 10(5) sites per cell, respectively. Competition studies with [(35)S]PSK-α and several synthetic PSK-α analogs demonstrated that only peptides that possesses mitogenic activity can effectively displace the radioligand. These results suggest that a signal transduction pathway mediated by peptide factors is involved in plant cell proliferation.